Kinerja Keuangan Daerah, Infrastruktur, dan Kemiskinan: Analisis Kabupaten/Kota di Indonesia 2006-2009 - Nugraheni, Diyah; Priyarsono, D. S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2012)
One important aspect of fiscal decentralization policy is delegation of authority and responsibility of management of public finance to regional governments, especially those of municipalities/districts. After more than ten years of implementation, it is now the right time to evaluate the policy questioning how effective its impacts on regional economic development. The study intends to find on how effective the performance of regional public finance is in providing basic infrastructures and how effective the provision of basic infrastructures reduces the poverty rates. By using panel data methods, this study confirms the positive relationship between performance of regional finance management and provision of basic infrastructures (especially those of road and electricity, but not that of drinking water). On the other hand, the relationship between the provision of basic infrastructures and poverty rates, as expected, is negative. This finding strengthens the belief that it is necessary to further enhance the basic infrastructures development to reduce poverty rates.